Macroeconomic Vulnerability in Developing Countries: Approaches and Issues - Seth, Anuradha (2012)
The increasing frequency and severity of financial and economic crises over the past three decades have raised important questions about the risk of economic growth being adversely impacted by crises (‘macroeconomic vulnerability’) and the appropriate policies needed to withstand and cope with such shocks (‘resilience’). (…)